Menuju Daya Saing UMKM dengan Kepemimpinan Digital - Denisa Fitriya ‘Uzzahra; Munawaroh Munawaroh (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
This study explores the role of digital leadership in enhancing competitiveness, focusing on the Ratu Lestari Women's Farmers Group (KWT) in Tegal Ratu Village. Using a survey approach and deskriptive statistical analysis, the research found a significant influence between digital leadership and competitiveness, with a correlation coefficient of 0.460 (p < 0.05). The results show that the more influential the digital leadership strategy implemented by MSMEs, the greater the impact on increasing competitiveness.